To what extent are maternal and child health, family planning, and nutrition policies supporting integrated service delivery in Burkina Faso, Côte d’Ivoire, and Niger? - Halima Tougri; Rachidatou Compaoré; Wambi Maurice Evariste Yameogo; Boukaré Congo; Abou Coulibaly; Danielle Yugbaré Belemsaga; Bertrand Meda; Denise Kpebo; Isabelle Bicaba; Marguerite Ndour; Jen Snell; Seni Kouanda (Archives of Public Health)
Abstract Background Service integration is a strategy to reduce maternal and infant mortality rates. “We analyzed the extent to which maternal and child health, family planning, and nutrition policies support the integration of maternal and child health services in Burkina Faso, Côte d’Ivoire, and Niger. Methods We performed a document review of policy documents on nutrition, family planning and maternal and child health using the READ approach (Ready materials, Extract data, Analyze data, Distill). We conducted a systematic search for documents among key informants interviewed at the central level and health centers. The Ten Key Principles for Successful Health Systems Integration of Suter’s framework were used for data analysis. Results The policy documents adopted a continuum of care approach and focused on mother, newborn, and child health (MNCH); family planning (FP); and nutritional needs throughout the course of life. However, in all three countries, most family planning and nutrition guidelines do not consider globality of care. These documents focus on the main themes of family planning and nutrition. None of the documents analyzed provided clear guidance on how providers should provide integrated MNCH, FP, and nutrition care to mother-child pairs in health centers. Conclusion Policy documents serve as practical guides for the provision of care in health centers. It is time to update national policies by including a vision of integrated service delivery for maternal and child health, family planning, and nutritional services.